Lowered Rhythm Tapping Ability in Patients With Constructional Apraxia After Stroke - Kobinata, Naomi; Yoshikawa, Hideto; Iwasaka, Yuji; Kawate, Nobuyuki (Frontiers in Neuroscience, 2020)
Rhythm tapping tasks are often used to explore temporal reproduction abilities. Many studies utilizing rhythm tapping tasks are conducted to evaluate temporal processing abilities with neurological impairments and neurodegenerative disorders. Among sensorimotor and cognitive disorders, rhythm processing abilities in constructional apraxia, a deficit in achieving visuospatial constructional activities, has not been evaluated. This study aimed to examine the rhythm tapping ability of patients with constructional apraxia after a stroke. Twenty-four patients were divided into 2 groups: with and without constructional apraxia. There were 11 participants in the constructional apraxia group and 13 in the without constructional apraxia group. The synchronization-continuation paradigm was employed in which a person performs a synchronized tapping activity to a metronome beat and continues tapping after the beat has stopped. For statistical analysis, a 3-way mixed analysis of variance (2×2×3) was conducted. The factors were groups (with and without constructional apraxia), tapping tasks (synchronization and continuation), and inter-stimulus intervals (600 ms, 750 ms, and 1000 ms). A significant effect of group factor was found (F[1,132] = 16.62; p < 0.001). Patients in the without constructional apraxia group were able to more accurately reproduce intervals than those in the constructional apraxia group. Moreover, a significant effect of tapping tasks was found (F[1,132] = 8.22; p < 0.01). Intervals were reproduced more accurately for synchronization tasks than continuation tasks. There was no significant inter-stimulus interval effect. Overall, these results suggest that there might be a relation between temporal and spatial reproductions in a wide spectrum of processing levels, from sensory perception to cognitive function.